2022
DOI: 10.7759/cureus.23479
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Risk Factors of Fear of Fall in the Elderly: A Hospital-Based, Cross-Sectional Study

Abstract: Background Falls are one of the most common but serious health issues faced by the elderly population. Falls-related injuries not only add to the morbidity and economic burden they also have a significant negative impact on psychological health and the quality of life of the elderly. In this study, we assess the prevalence of fear of falling among the geriatric population and the risk factors associated with fear of falling. Methodology This prospective, cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Reports from other countries have shown a higher prevalence of FOF among residents in institutions. 28 No Open access 29 Studies from other parts of the world have reported a higher prevalence of FOF among the older people living in institutional settings than those living in communities. 28 30 31 However, the results from studies done in highincome countries cannot be extrapolated to India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from other countries have shown a higher prevalence of FOF among residents in institutions. 28 No Open access 29 Studies from other parts of the world have reported a higher prevalence of FOF among the older people living in institutional settings than those living in communities. 28 30 31 However, the results from studies done in highincome countries cannot be extrapolated to India.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a 42% prevalence of FOF among the older people in a hospital setting in India. 29 …”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Falls are the most common form of domestic injuries in many studies, and also women are affected the most. [ 22 23 ] So, be it a rural or urban locality on an average 1/3 rd of the elderly were prone to domestic accidents as shown in many studies listed above.…”
Section: Discussionmentioning
confidence: 99%
“…in Uttarakhand, 42% of the elderly subjects had a history of fear of fall and it was more among females compared to males. [ 23 ] This study had a slight high prevalence of a history of fear of falls, as it is done in a tertiary healthcare hospital to which much of the times diseased individuals will be attending the outpatient departments. A systematic review by Biswas et al , which included 22 studies, found the similar fall incidence and risk among the elderly in India.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have been conducted regarding the risk factors for FOF and its relationship with fall risk in stroke patients [14][15][16][17][18][19]; they suggested that FOF is a critical indicator of falling; however, these studies investigating the connection between FOF and fall risk lack theoretical underpinnings explaining how physiological and psychological factors induce FOF and fall risk, and they are not supported by detailed assessments of relevant constructs [15,18]. Theory-based and extensive investigations are needed to develop a further understanding of what FOF means to older stroke patients.…”
Section: Introductionmentioning
confidence: 99%